Exercise Dose Effects on Body Fat 12 Months after an Exercise Intervention: Follow-up from a Randomized Controlled Trial - Christine M. Friedenreich; Yibing Ruan; Aalo Duha; Kerry S. Courneya (Hindawi Limited, 2019)
Background. Exercise interventions can result in weight loss, which is associated with reductions in disease risk. It is unknown how the volume of exercise prescribed in a one-time exercise intervention impacts long-term body fatness. We compared 24-month body fat changes among postmenopausal women previously prescribed 300 versus 150 minutes/week of exercise in a year-long exercise intervention trial. Methods. The Breast Cancer and Exercise Trial in Alberta (BETA) was a two-centred randomized controlled trial in Alberta, Canada. The trial consisted of a 12-month intervention and 12-month observation period. For the intervention, participants were randomized to either a moderate-volume exercise group (150 min/week) or a high-volume exercise group (300 min/week). Participants in this study were 334 inactive postmenopausal women who had been followed-up to 24 months. The primary outcome for this study was 24-month change in total body fat using dual energy X-ray absorptiometry scans. Other measures included weight, waist and hip circumferences, subcutaneous and intra-abdominal fat from computed tomography scans, and lean mass. Researchers were blinded to randomization group when measuring body fat. Results. Both groups self-reported ∼180 minutes/week moderate-vigorous activity at 24 months. No statistically significant difference was found in total body fat at 24 months between the two groups. Statistically significant effects (comparing high versus moderate groups) were found for BMI (least-square mean change (95% CI): −0.66 (−0.97, −0.36) versus −0.25 (−0.55, 0.05) kg/m2, P=0.04), waist-to-hip ratio (−0.033 (−0.040, −0.026) versus −0.023 (−0.030, −0.016), P=0.05), and subcutaneous abdominal fat area (−32.18 (−39.30, −25.06) versus −22.20 (−29.34, −15.05) cm2, P=0.04). Conclusion. Prescribing 300 versus 150 minutes/week of exercise to inactive postmenopausal women resulted in some long-term greater decreases in measures of body composition but no overall differences in total body fat loss. This trail is registered with NCT01435005.